Environmental Management - Pollution, Habitat, Ecology, and Sustainability - John P. Tiefenbacher (IntechOpen, 2022)
Environmental Management - Pollution, Habitat, Ecology, and Sustainability includes sixteen chapters that discuss pressing environmental issues in diverse locations around the world. Chapters discuss methods, technologies, analyses, and actions that may enlighten and enable decision-makers and managers in their quests for control of environmental problems. The authors present the facts and the challenges behind the assorted issues and offer new perspectives for contending with natural, social, economic, and political aspects of management.